A detailed in vivo analysis of the retinal nerve fibre layer in choroideremia - Fu, D; Xue, K; Jolly, J; Maclaren, R (Wiley, 2018)
Purpose Choroideremia is a currently incurable X‐linked recessive retinal degeneration that leads to blindness. Gene therapy approaches to date target the outer retinal layers. However, the choroideremia (CHM) gene is expressed in all retinal layers, and a previous study on a small cohort of choroideremia patients suggested possible thinning of the retinal nerve fibre layer (RNFL). The purpose of the study was to examine the RNFL in detail using advanced imaging techniques in a larger cohort of choroideremia patients. Methods Spectral domain optical coherence tomography of the peripapillary RNFL acquired with the Heidelberg Spectralis HRA circular scan mode were analysed retrospectively in 41 eyes of 21 choroideremia patients aged 39.6 years (±3.7 SEM). As age‐matched controls, 20 eyes from 10 patients with retinitis pigmentosa and 56 eyes from 28 healthy individuals were also assessed. Automated RNFL segmentation was adjusted manually to precisely delineate the RNFL. The data were also compared against an external normative database. Results Mean peripapillary RNFL thickness in choroideremia was 130 ± 3 μm in the right eye (OD) and 133 ± 3 μm in the left eye (OS). This was 24% and 27% thicker than RNFL thickness in the controls (p < 0.001 for both). Patients with retinitis pigmentosa also showed an increase in RNFL thickness, which was no different to the choroideremia cohort (p > 0.05). Compared with manual analysis, the automated function of the inbuilt software was consistently inaccurate in segmenting the RNFL in choroideremia. Conclusion The RNFL is significantly thicker in choroideremia compared with age‐matched normal controls, which was similar to what was seen in retinitis pigmentosa.